Remembering Donald F. Steiner - Weiss, Michael A.; Chan, Shu Jin (Frontiers in Endocrinology, 2015)
Pioneering endocrinologist and molecular biologist Donald Frederick Steiner, A. N. Pritzker Distinguished Service Professor of Medicine and Biochemistry & Molecular Biology at the University of Chicago (Fig. 1), died on November 11, 2014 at the age of 84. “Very few scientists,” observed Nobel Laureate Joseph L Goldstein, M.D., Chairman of the Department of Molecular Genetics at the University of Texas (UT) Southwestern Medical Center, “can lay claim to original research that has stood the test of time in both the biological and clinical arenas.” Steiner’s contributions meet this dual standard. Dr. Steiner was also renowned for his mentorship of successive generations of leaders in biochemistry and academic medicine.